The Commitment to Disaster Risk Reduction as a Bridge between Humanitarian Aid and Sustainable Development. Issue 4 (19th September 2017) - Pusterla, Francesca
Abstract : Through analyses of both books, the clear lesson is obtained that the complexity and diversity of intervention scenarios do not allow humanitarian aid and sustainable development to be conceived as separate worlds any longer. The two books help us perfectly to understand this and provide interesting and innovative perspectives to decrease the vulnerability of the most environmentally and humanly fragile areas.